Outcomes of Planned Home Visits of Intern Public Health Nurses: An Example from Turkey - Ozlem Ozkan; Saadet Ozdemir (Ubiquity Press, 2017)
Objective This study aimed at evaluating the outcomes of planned home visits of intern public health nurses enrolled to a school of health over 8 educational years. Method The descriptive research consisted of 181 families (N = 745 individuals) who received primary services through the planned home visits undertaken by 431 intern public health nurses at Kocaeli province in Turkey. The data were collected from Family Nursing Process Records and Family Health Achievement Forms. Both of these data collection forms were classified according to North American Nursing Diagnosis Association (NANDA) Taxonomy II. Results Intern public health nurses provided primary health services to 181 families (N = 745 persons) with a total of 8771 planned home visits undertaken over 802 days and 14.874 student/practice days. A total of 1539 nursing diagnoses were identified and 1677 achievements about these diagnoses were reported. Nursing diagnosis per family and per individual turned out to be 8.50 and 2.1, respectively, and achievements were 9.3 per family and 2.3 per individual. Among the nursing diagnosis domains, health promotion (20.3%), safety/protection (16.8%), and activity/rest (16.0%) were the top 3 domains identified. The most common diagnoses turned out to be ineffective health maintenance (47.4%) in health promotion domain and risk for trauma (18.2%) in safety/protection domain. The achievements were reported most in health promotion (37.9%), activity/rest (17.6%), and safety/protection (9.6%), respectively. Conclusions Planned and continuous home visits by intern public health nurses resulted in positive health achievements in families, especially for women and children.